Exploring Ethnic Differences in Toxicity in Early-Phase Clinical Trials for Oncology Drugs. (September 2014) - Ogura, Takashi; Morita, Satoshi; Yonemori, Kan; Nonaka, Takahiro; Urano, Tsutomu
During oncology drug development, it is important that ethnic differences are evaluated to determine the optimal dose and administration schedule in a new region based on the clinical data from other regions. The objective of this study was to explore the possibility of detecting ethnic differences in toxicity during early-phase clinical trials. Data were reviewed from phase I clinical trials for new drug applications conducted in Japan and Western countries. The maximum tolerated doses (MTDs), recommended phase II doses (RP2Ds), and approved doses in Japan were compared with those in Western countries. There were 4 of 28 drugs eligible for analysis that showed differences in MTDs or RP2Ds between Japanese and Western patients. Differences in MTDs or RP2Ds in 2 phase I trials were associated with ethnic differences in toxicity. It may be worthwhile to evaluate ethnic differences in toxicity during early-phase clinical trials for oncology drugs.